2020
DOI: 10.3390/biomedicines8120612
|View full text |Cite
|
Sign up to set email alerts
|

Anti-c-myc RNAi-Based Onconanotherapeutics

Abstract: Overexpression of the c-myc proto-oncogene features prominently in most human cancers. Early studies established that inhibiting the expression of oncogenic c-myc, produced potent anti-cancer effects. This gave rise to the notion that an appropriate c-myc silencing agent might provide a broadly applicable and more effective form of cancer treatment than is currently available. The endogenous mechanism of RNA interference (RNAi), through which small RNA molecules induce gene silencing by binding to complementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 111 publications
0
16
0
Order By: Relevance
“…Unfortunately, the trial did not meet expectations of Myc knockdown or efficacy and was discontinued. For a recent review on the subject, please refer to Habib et al (2020) .…”
Section: Blocking Myc Translationmentioning
confidence: 99%
“…Unfortunately, the trial did not meet expectations of Myc knockdown or efficacy and was discontinued. For a recent review on the subject, please refer to Habib et al (2020) .…”
Section: Blocking Myc Translationmentioning
confidence: 99%
“…Liposomes were initially identified in the 1960s following the spontaneous formation of closed lipid bilayers in water [ 52 ]. It remains a popular choice for lipid-based vehicles because of its simple structure [ 53 ]. These NPs are composed of an aqueous core that encapsulates the drug or gene of choice and is enclosed in a unilamellar or multilamellar phospholipid bilayer that contains both hydrophilic and hydrophobic groups ( Figure 3 ) [ 54 ].…”
Section: Nanomedicinementioning
confidence: 99%
“…The c-Myc gene encodes a proto-oncoprotein, a widely recognized transcription factor regulating approximately 10–15% of genes implicated in cell proliferation, differentiation, apoptosis and other processes ( Friedman et al, 2017 ; Habib et al, 2020 ), and c-Myc mutations are often associated with tumors ( Berns et al, 1997 ; Brodsky and McCracken, 1999 ; Hermeking et al, 2000 ; Morrish et al, 2003 ; Wilson et al, 2004 ). Recently, it has been reported that USP13 is co-overexpressed with c-Myc in many tumors, such as NSCLC ( Wu et al, 2019 ), cholangiocarcinoma (CAA) ( Zhou et al, 2020 ), GSCs ( Fang et al, 2017 ), and hepatocellular carcinoma (HCC) ( Huang et al, 2020 ).…”
Section: Cellular Function Of Usp13mentioning
confidence: 99%